Two cases of multiple ossifying fibromas in the jaws - Wang, Ting-Ting (BioMed Central, 2014)
BACKGROUND: The clinicopathologic characteristics of multiple ossifying fibroma (OF) are unclear due to the condition’s rarity, making diagnosis challenging. Sporadic multiple OFs must be distinguished from hyperparathyroidism-jaw tumour syndrome (HPT-JT) related OF and other fibro-osseous lesions. METHODS: Multiple OF cases were identified from ossifying fibroma cases. Clinical data including age, sex, anatomic site, radiographic features, clinical impression, treatment and available follow-up data as well as serum calcium, phosphorus, and parathyroid hormone (PTH) were recorded. GNAS and HRPT2 genetic mutations were examined in the two present cases. Case reports of sporadic multiple ossifying fibroma and HPT-JT-related OF were also reviewed. RESULTS: The two present cases were confirmed as sporadic multiple OF, with no genetic GNAS and HRPT2 mutations found. The incidence of sporadic multiple ossifying fibroma was 2.0% (2/102). The total 18 sporadic multiform OF cases were characterized as followed: 13 (72.2%) female; 5 (27.8%) male; mean age 28.6 years; 2/16 (11.1%) cases only in the mandible; 4/18 (22.2%) cases only in the maxilla; and 12/18 (66.7%) cases in both the maxilla and mandible. Radiographically, the lesions were radiolucent in 5/18 (27.8%) cases and mixed density in 13/18 (72.2%) cases. Along with 24 cases of HPT-JT related OF were reviewed, sixteen (66.7%) patients were diagnosed with a single lesion, and 8 patients (33.3%) were diagnosed with multiple jaw lesions. CONCLUSIONS: Sporadic multiple OFs are very rare, but must be distinguished from HPT-JT related OF. We strongly recommend that patients diagnosed with multiple ossifying fibromas receive serum PTH testing and mutation screening of HRPT2. VIRTUAL SLIDES: http://www.diagnosticpathology.diagnomx.eu/vs/1194507146115753